2020
DOI: 10.18844/wjet.v12i3.4978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MoblrN m-learning system: Participants' attitudes and opinions

Abstract: The advance of pervasive technologies such as mobile technologies and various mobile devices has brought opportunities for educators to design and perform interactive learning activities and has also enabled educationalists to access the virtual learning environment anytime and anywhere without restrictions of time or place and without too much additional effort. The m-learning system, MobLrN, has been developed by the researcher. Different from the m-learning systems developed by other researchers, the MobLrN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…From the encouraging and promising estimations gained in the study, it is shown that end-user and database administrators of POSSA do not have any trouble in retrieving the required information and local data on the designed and integrated extension module whenever they need it without more effort; and its validity is approved based on [23]. In order to get the opinions and perceptions of participants on the quality attributes of the designed and developed am_ET extension, the survey considers for its functionality, reliability, usability, efficiency and maintainability as it could be adopted from Cavus [24]. The assessment of the localization applications is specifically relevant; however, few researchers have addressed these measurement criteria using laboratory experimental studies with database administrators and end-users in real areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the encouraging and promising estimations gained in the study, it is shown that end-user and database administrators of POSSA do not have any trouble in retrieving the required information and local data on the designed and integrated extension module whenever they need it without more effort; and its validity is approved based on [23]. In order to get the opinions and perceptions of participants on the quality attributes of the designed and developed am_ET extension, the survey considers for its functionality, reliability, usability, efficiency and maintainability as it could be adopted from Cavus [24]. The assessment of the localization applications is specifically relevant; however, few researchers have addressed these measurement criteria using laboratory experimental studies with database administrators and end-users in real areas.…”
Section: Discussionmentioning
confidence: 99%
“…User acceptance testing was conducted to evaluate Amharic locale extension functionalities which was done based on the ISO 9241-11 usability testing characteristics, such as efficiency, effectiveness (referring the completeness and accuracy) and user satisfaction and the enquiry of the usability methods of any developed system must be validated alongside potential users [23]. This paper proposed different criteria for evaluating the quality of a developed system and finally adapted suitable criteria from Cavus [24] that best fits the developed module to evaluate its efficiency, usability, and reliability. These assessment methods and techniques are presented with respect to each development phase of the extension module.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…(S05) MoblrN: a mobile learning system that offers an m-learning environment with access control, user profile, learning materials, assignments, self-test, announcements, performance, and report generation. The application was built using PHP, Java, and MySQL (Cavus, 2020).…”
Section: Arrangement Processmentioning
confidence: 99%
“…Los avances de tecnologías han ofrecido oportunidades para que los educadores sean creadores de actividades interactivas. También les han permitido tener acceso a un entorno educativo virtual sin restricciones de lugar, tiempo, o bien replantear metodologías de enseñanza desde una perspectiva tecnológica de TIC, lo cual se viene a traducir como TAC (Alvarez et al, 2020;Castro, 2005;Cavus, 2020;& Nivela, 2018). En tal respecto, existen contextos sociales de pensamiento progresista en los cuales el avance tecnológico es percibido por ser un progreso humanista, donde las tecnologías frecuentemente aclaman igualdad.…”
Section: Introductionunclassified